Compassionate Use of Omadacycline in a Down Syndrome Pre-Schooler With Critically Ill Atypical Pneumonia Caused by Macrolide-Resistant Mycoplasma Pneumoniae - Wu D; Xie FJ; Wang YJ; Jiang XH; Zhang GL; Zhang H; Zhu YC; Zhang Y; Tang YJ; Lin YL; Xu JX; Zhang JN; et al. (Infection and Drug Resistance)
Di Wu,1,* Feng-Jie Xie,2,* Ya-Jun Wang,3,* Xiao-Hui Jiang,1,* Guo-Li Zhang,3,* Hong Zhang,2 Yu-Cheng Zhu,4 Yan Zhang,4 Yu-Jia Tang,1 Yi-Lu Lin,1 Jia-Xi Xu,5 Jia-Ning Zhang,5 Bo-Wen Liu,5 Kai Kang,5 Yang Gao1 1Department of Critical Care Medicine, The Sixth Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang Province, People’s Republic of China; 2Department of Critical Care Medicine, The Hongqi Hospital Affiliated to Mudanjiang Medical University, Mudanjiang, Heilongjiang Province, People’s Republic of China; 3Department of Pediatrics, The Sixth Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang Province, People’s Republic of China; 4Department of Critical Care Medicine, The Hongxinglong Hospital of Beidahuang Group, Shuangyashan, Heilongjiang Province, People’s Republic of China; 5Department of Critical Care Medicine, The First Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kai Kang, Department of Critical Care Medicine, The First Affiliated Hospital of Harbin Medical University, 23 Youzheng Street, Nangang District, Harbin, Heilongjiang Province, 150001, People’s Republic of China, Tel +86-13904618016, Email janekk79@126.com Yang Gao, Department of Critical Care Medicine, The Sixth Affiliated Hospital of Harbin Medical University, 998 Aiying Road, Songbei District, Harbin, Heilongjiang Province, 150027, People’s Republic of China, Tel +86-13045160709, Email gaoyang0312@126.comBackground: Rapid and accurate identification of causative organisms and prompt initiation of pathogen-targeted antibiotics are crucial for managing atypical pneumonia. The widespread application of targeted next-generation sequencing (t-NGS) in clinical practice demonstrates significant targeted advantages in rapid and accurate aetiological identification and antimicrobial resistance genes detection, particularly for difficult-to-culture, rare, or unexpected pathogens. An alarming surge of acquired macrolide resistance (MR) in Mycoplasma pneumoniae (MP) presents a substantial challenge for the clinical selection of pathogen-targeted antibiotics worldwide, especially for fluoroquinolone-restricted pediatric patients with limited options available.Case Presentation: In this case report, we present for the first time the compassionate use of omadacycline (OMC) in a Down syndrome pre-schooler with critically ill atypical pneumonia caused by macrolide-resistant MP. The treatment achieved a favourable therapeutic effect without any related adverse events (AEs) during hospitalization and follow-up.Conclusion: In clinical practice, rapid and accurate identification of causative organisms should be a priority for prompt initiation of pathogen-targeted antibiotics, in which tNGS possesses enormous potential, particularly for difficult-to-culture MP. At present, OMC is not recommended in the package insert for clinical application in pediatric patients under 8 years of age due to potential age-specific AEs on tooth colour and development as well as bone growth. The superior efficacy and safety of OMC in the management of critically ill atypical pneumonia caused by macrolide-resistant MP were comprehensively documented in this Down syndrome pre-schooler, which merits future well-designed studies to validate our findings, enhance understanding of the features of OMC, and further expand its clinical application in preschool-aged patients.Keywords: omadacycline, pre-schooler, down syndrome, macrolide-resistant mycoplasma pneumoniae, atypical pneumonia, targeted next generation sequencing, aetiological identification, antimicrobial resistance gene detection